Functional Exercise Performance in Children with Cerebral Palsy: Is the 1-Minute Sit-to-Stand Test an Alternative to the 6-Minute Walk Test? - Ergun, Betul; Baykan Copuroglu, Ozge; Baykan, Muge; Gurer, Feyza; Abakay, Hanife (Taylor & Francis Inc, 2026)
Objectives This study examined the validity, test-retest reliability, and clinical feasibility of the 1-minute sit-to-stand test (1MSTS) as a practical alternative to the 6-minute walk test (6MWT) for assessing functional exercise capacity in children with cerebral palsy (CP). Methods Seventy-eight children aged 5-18 years with spastic hemiplegic CP (Gross Motor Function Classification System I-II) completed the 1MSTS and 6MWT in random order on the same day. Test-retest reliability of the 1MSTS was evaluated using the intraclass correlation coefficient (ICC), standard error of measurement (SEM), and minimal detectable change (MDC). Construct validity was assessed using correlation and linear regression analyses. Results The 1MSTS demonstrated good test-retest reliability (ICC = 0.78), with an SEM of 1.49 repetitions and an MDC95 of 4.12 repetitions. A very strong association was observed between 1MSTS and 6MWT performances (rho = 0.886, p < .001). Linear regression analysis further demonstrated that 6MWT distance explained approximately 80% of the variance in 1MSTS repetitions (R-2 = 0.799). These findings indicate that the 1MSTS captures functional exercise capacity assessed by the 6MWT. Conclusion The 1MSTS is a valid, reliable, and clinically feasible alternative to the 6MWT for evaluating functional exercise capacity in children with spastic hemiplegic CP. Trial registrationClinicalTrials.gov (NCT07136129).
Keywords: Cerebral Palsy; Functional Exercise Capacity; Sit-To-Stand Test; Test-Retest Reliability